Effects of Soil Chemistry on the Physico-Chemical Characteristics of the Grains of Adlay (Coix lacryma-jobi Linn) Grown in Bukidnon, Philippines - Coludo, Felvin E.; Janairo, Gerardo C. (Annals of Tropical Research, 2015)
The amounts of P, K, Ca, Mg, Na, Fe, Zn, Mn, Cu, B, Pb, and Cd in both grits and hull/testa of Adlay (Coix lacryma-jobi L., Gulian variety) in Bukidnon, Philippines, were quantified relative to the pH, electrical conductivity (EC), cation-exchange capacity (CEC), and amounts of organic matter (OM), N, P, K, Ca, Mg, Na, Fe, Zn, Mn, Cu, B, Pb, and Cd of the soils where these plants were grown. The P, K, Ca, Fe, and Cu contents in grits were differentiated by P, CEC, Ca, Fe, and Zn of the soil, respectively. The accumulations of both Mg and Zn in grits were influenced only by the pH of the soil while the Mn contents in grits were influenced by both pH and Mn content of the soil. The Fe, Zn, and B contents of hull/testa were significantly differentiated by the Zn, Fe and OM of the soil, respectively. The mean amounts of macroelements in both grits and hull/testa were in the order of K>P>Mg>Ca. The mean micro-element contents in grits were in the order of Fe>Na>Mn>Zn>Cu>B, while for hull/testa, Fe>Na>Mn>Zn>B>Cu. The Pb contents in grits and hull/testa were below the detection limit of the method while the amounts of Cd in both grits and hull/testa were below the permitted maximum level of the Joint FAO/WHO Food Standards Programme-Codex Committee on Contaminants in Food. From the amounts of these elements in Adlay, this indigenous crop may well be a good alternative food crop for human and animal consumption.